183 DISTRIBUTION AND METABOLIC SYNDROME CORRELATES OF SERUM ALANINE AMINOTRANSFERASE IN CHILDREN AND ADOLESCENTS: THE BOGALUSA HEART STUDY. Issue 1 (1st January 2007) - Patel, D. A.; Srinivasan, S. R.; Xu, J.; Chen, W.; Berenson, G. S.
Abstract : Background: Abnormal levels of serum alanine aminotransferase (ALT), a marker of liver dysfunction and nonalcoholic fatty liver (NAFL), are considered the metabolic consequence of obesity in adults and children alike. However, population-based data on the distribution of ALT and its association with obesity and other components of metabolic syndrome in biracial (black-white) children and adolescents are lacking. Methods: The study sample consisted of 1, 524 children (age 4-11 years, 62% white, 51% male) and 1, 060 adolescents (age 12-18 years, 58% white, 51% male), examined as part of the Bogalusa Heart Study, with measurements of ALT and other CV risk factor variables. Results: ALT levels showed significant race (white > black, p < .0001) in children and gender (male > female, p = .0001) difference in adolescents. Both in children and adolescents, top versus bottom quartiles of ALT levels had increased prevalence of adverse levels (> than age, race, gender-specific 75th percentile) of body mass index (BMI), systolic blood pressure, total-to-HDL cholesterol ratio, insulin resistance index (HOMA-IR), as well as metabolic syndrome. In multivariate analyses, BMI was the major predictor of ALT levels in both children and adolescents. Other significant independent predictors were white race in children and total-to-HDL cholesterol ratio, HOMA-IR, and male gender in adolescents. Clustering of adverse levels of three or four risk factors (BMI, systolic blood pressure, total-to-HDL cholesterol, or HOMA-IR) at the top quartile of ALT was displayed by 24.9% children and 29.0% adolescents and was significantly higher than expected by chance alone ( p < .05-< .01). Moreover, area under the receiver operating curve values to determine the ability of ALT in classifying individuals with metabolic syndrome were 0.67 and 0.82 in children and adolescents, respectively. Conclusion: ALT levels within normal range are strongly associated with metabolic syndrome and its components in children and adolescents and thus may be a useful biomarker for this condition.